Genetic Polymorphisms and the Risk of Infection Following Esophagectomy. Positive Association with TNF-α Gene −308 Genotype - Azim, Kaukab (2007)
OBJECTIVE: To examine the association of single nucleotide polymorphisms (SNPs) in inflammation-related genes in the development of infections following esophagectomy. SUMMARY BACKGROUND DATA: Genetic polymorphisms for immunoregulatory cytokines may explain individual variation in response to trauma. Esophagectomy is associated with a high risk of postoperative infection and sepsis, and this study explored a number of SNPs in cytokine genes and their relationship to postoperative infection. METHODS: In a prospective analysis of 197 patients with esophageal cancer undergoing resection, 55 developed postoperative infections. DNA was extracted and genotyping was performed for polymorphisms in genes encoding TNF-α, IL-1β, IL-1 receptor antagonist, IL-10, and Toll-like receptor 4 (TLR-4) using Taqman chemistry and PCR/RFLP. In a blinded analysis, the cohort with infections was compared with the no complication cohort (n = 114) and a cohort that had noninfective complications (n = 28). RESULTS: No differences in polymorphisms for IL-1β, IL-1 RN, IL-10, and TLR-4 genes were observed across groups. The frequency of TNF-α −308 GG homozygotes was significantly (P = 0.021) higher in the postoperative infection group. The G allele was significantly higher in the postoperative infection group compared with the no complication group (P = 0.017) and other complication group (P = 0.013). By multivariate analysis, this polymorphism as well as age and body mass index were predictors of infection. CONCLUSION: The TNF-α −308A allele has been shown to be associated with higher circulating levels of TNF-α and the −308 G allele is a comparative low secretor allele. We propose that the polymorphism in the promotor region of TNF-α gene may lead to altered expression and a possible suboptimal activity of TNF-α in persons with GG genotypes, and these data suggest a link with infection following major surgery.